Drug therapy for the prevention and treatment of bronchopulmonary dysplasia - Iyengar, Anjali; Davis, Jonathan M. (Frontiers in Pharmacology, 2015)
Introduction: As more infants are surviving at younger gestational ages, bronchopulmonary dysplasia (BPD) remains as a frequent neonatal complication occurring after preterm birth. The multifactorial nature of the disease process makes BPD a challenging condition to treat. While multiple pharmacologic therapies have been investigated over the past two decades, there have been limited advances in the field. Often multiple therapies are used concurrently without clear evidence of efficacy, with potential for significant side effects from drug-drug interactions. Methods: Systematic literature review. Conclusion: Although there is physiologic rationale for the use of many of these therapies, none of them has single-handedly altered the incidence, severity, or progression of BPD. Future research should focus on developing clinically significant end-points (short and long term respiratory assessments), investigating biomarkers that accurately predict risk and progression of disease, and creating appropriate stratification models of BPD severity. Applying a multi-modal approach to the study of new and existing drugs should be the most effective way of establishing the optimal prevention and treatment regimens for BPD.